Size and Zeta Potential Clicked Germination Attenuation and Anti-Sporangiospores Activity of PEI-Functionalized Silver Nanoparticles against COVID-19 Associated Mucorales (Rhizopus arrhizus) - Tiwari A.K.; Gupta M.K.; Pandey G.; Tilak R.; Narayan R.J.; Pandey P.C. (My University, 2025)
The SARS-CoV-2 infections in Indian people have been associated with a mucormycotic fungal infection caused by the filamentous fungi Rhizopus arrhizus. The sporangiospores of R. arrhizus are omnipresent in the environment and cause infection through inhalation or ingestion of contaminated air and foods. Therefore, the anti-sporangiospore activity of polyethyleneimine functionalized silver nanoparticles (PEI-f-Ag-NPs) with variable size and surface charge as a function of the molecular weight of PEI was explored. The results showed that both PEI-f-AgNP-1 and PEI-f-AgNP-2, potentially, attenuated the germination and reduced the viability of sporangiospores. Furthermore, the results showed that the minimum inhibitory concentration (MIC) values of both PEIf-AgNP-1 and PEI-f-AgNP-2 (1.65 and 6.50 μg/mL, respectively) were dependent on the nanoparticle size and surface ζ potentials. Similarly, the sporangiospore germination inhibition at MIC values was recorded, showing 97.33% and 94% germination inhibition, respectively, by PEI-f-AgNP-1 and 2 within 24 h, respectively. The confocal laser scanning microscopy, SEM-EDS, and confocal Raman spectroscopy investigation of PEI-f-Ag-NPs treated sporangiospores confirmed size and surface charge-dependent killing dynamics in sporangiospores. To the best of our knowledge, this is the first investigation of the polyethyleneimine functionalized silver nanoparticle-mediated size and surface charge-dependent anti-sporangiospore activity against R. arrhizus, along with a possible antifungal mechanism. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.